Deceiving the Queen: Integrating Jambinese Traditional Honey Gathering into Science Learning - Bambang Hariyadi; Dwi Agus Kurniawan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2018)
Traditional honey gathering is performed by most Malay communities in Jambi Province, Indonesia. The process of honey gathering is not merely taking honey, and other associated products such as wax, but has also developed into an important cultural ritual, and even become a part of the identity of the Jambi Malay community. Traditional honey gathering also involves values ​​and local knowledge that can enrich science teaching and learning. This study aims to reveal the science content of traditional honey gathering in Jambi. Data were collected through participatory observations as well as a literature review. The results show that the traditional honey gathering can be integrated into teaching to create more meaningful science learning, especially in junior high school. The integration can be implemented by employing constructivist based learning models that are adjusted to the students’ conditions and the environment around their schools. Keywords: local knowledge, traditional honey gathering, science learning ABSTRAK Pengambilan madu secara tradisional dilakukan oleh sebagian besar masyarakat melayu di Propinsi Jambi. Prosesi pengambilan madu tidak semata-mata hanya untuk mendapatkan madu atau pun produk lain yang terkait madu seperti malam (lilin), tetapi sudah berkembang menjadi budaya bahkan menjadi identitas masyarakat Melayu Jambi. Pengambilan madu secara tradisional juga mengandung nilai-nilai dan pengetahuan yang dapat diintegrasikan dalam pembelajaran sains. Penelitian ini bertujuan untuk menyingkap aspek ethnosains dari tradisi pengambilan madu pada masyarakat Melayu Jambi. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam (in-depth interview), serta kajian literatur. Hasil penelitian menunjukkan bahwa pengambilan madu tradisional dapat diintegrasikan untuk menciptakan pembelajaran IPA di SMP yang lebih bermakna. Dalam implementasinya, pembelajaran dapat dilakukan dengan model-model pembelajaran yang berbasis konstruktivisme, sesuai dengan kondisi siswa dan lingkungan di sekitar sekolah. Kata kunci: Pengetahuan lokal, pengambilan madu tradisional, pembelajaran sains